Dakwah Berbasis Konten Lokal: Analisis Ceramah Adat Basandi Syarak, Syarak Basandi Kitabullah - Putra Chaniago (JURNAL ILMIAH SYI'AR, 2020)
The main problem in this research is the analysis based on local content analysis on the video of the lectures traditional of adat basandi syarak, syarak basandi kitabullah by Ustadz Zulhamdi Lc, MA. Researchers want to know how a discourse is built in a culture-based da'wah conducted by religious scholars in Minangkabau. This type of research is qualitative descriptive, using documentation studies as a data collection technique. Then use the method of discourse analysis Teun van Dijk. The findings of the study show that the customary lecture of adat basandi syarak, syarak basandi kitabullah by Ustadz Zulhamdi Lc, MA is seen from the aspect of social analysis, text and social cognition, namely building a religious discourse, amar ma'ruf nahi mungkar. Departing from the concerns of the scholars in an effort to maintain the Islamic tradition and strengthen the character of the Minangkabau people known as the state of the scholars, amid the issues of moral and mental damage to Minangkabau youth today. Local content-based da'wah through a long-believed philosophy of life, becomes a solution to return to the order of life in accordance with the expectations of the ancients who lived in a strong religious tradition fortifying themselves and generations of mental and moral decline. Da'wah is a flexible and universal activity, so with local content-based da'wah can be a solution to the problems that occur in the community under its auspices.